System Perkawinan Matrilineal Di Suku Fehan Kabupaten Malaka - Maria contasya ingraini atitus; Noviani Vieaney; Stefanus Don Rade (Pusat Riset dan Inovasi Nasional, 2024)
Marriage according to article 1 of law number 1 of 1974 concerning marriage. What is meant by marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on BELIEF IN THE ALMIGHTY GOD.This matrilineal marriage itself is known as